2020
DOI: 10.3389/fped.2020.00196
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Environmental Health, Ecosystem Vitality, and Early Childhood Caries

Abstract: Background: Environmental issues lead to serious health problems in young growing children. This study aims to determine the association between a country's level of environmental health, ecosystem vitality, and prevalence of early childhood caries (ECC). Methods: This was an ecological study. The data for the explanatory variables-country-level environmental performance index (EPI), environmental health, and ecosystem vitality-were obtained from the Yale Center for Environmental Law and Policy. The outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Programs/actions increasing GDP (PPS) per capita are expected to effectively contribute to the reduction in the disease burden at national level, especially in Eastern countries of Europe. This contradicts the results of a recent association study, where better ecosystem vitality was associated with lower ECC risk, through the rational use of resources, healthy lifestyles, and preventive health practices [ 41 ]. However, lower incidence in Western countries is unsurprising, as the stronger the economic force, the more funds allocated to healthcare, which may facilitate the provision of preventive services [ 42 ].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Programs/actions increasing GDP (PPS) per capita are expected to effectively contribute to the reduction in the disease burden at national level, especially in Eastern countries of Europe. This contradicts the results of a recent association study, where better ecosystem vitality was associated with lower ECC risk, through the rational use of resources, healthy lifestyles, and preventive health practices [ 41 ]. However, lower incidence in Western countries is unsurprising, as the stronger the economic force, the more funds allocated to healthcare, which may facilitate the provision of preventive services [ 42 ].…”
Section: Discussioncontrasting
confidence: 80%
“…Thus, our results indicate that GDP per capita is a more useful indicator than risk of poverty rate in determining the oral health in population. Nevertheless, GDP and urbanization have to be taken into consideration as possible factors that affect population health [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emission levels of the gas are higher in developed countries than in developing countries [28]. Poor regulation of nitrous oxide in industrialized urban environments may be a factor accounting for an association between nitrous oxide emission levels and ECC [3].…”
Section: Discussionmentioning
confidence: 99%
“…One such study investigated the association between ecosystem vitality, environmental health, and early childhood caries (ECC), which is any caries experience of the primary teeth in children < 72 months of age [2,3]. The study identified an inverse and significant association between ECC in 3-5-year-olds and ecosystem vitality, and a direct but non-significant association between ECC prevalence and environmental health [3]. However, the study determined these associations by using composite ecosystem vitality and environmental health scores.…”
Section: Introductionmentioning
confidence: 99%
“…Family-level factors, such as socio-economic aspects, are associated with ECC [8]. Community-level factors such as environment, poverty, maternal well-being, dental care access and universal dental coverage are also related to ECC prevalence [9]. Research has also demonstrated that ECC is associated with other common childhood diseases, and shares similar risk factors with other non-communicable diseases [10].…”
Section: Introductionmentioning
confidence: 99%